Textile Industrial Effluents: Implication and Possible Use for Afforestation in Western Rajasthan - Aggarwal, R K; Kumar, Praveen (Annals of Arid Zone, 2016)
In this paper, the environmental problems related to industrial effluents with particular reference to western Rajasthan are discussed. In Jodhpur district alone, textile effluents constituting major source are discharged untreated at the rate of 7 million litres/day. The effluents are coloured with high pH (9-11), predominant in sodium (600-3500 ppm) having high RSC values (11-90 me/I), very low in calcium, magnesum, lead and cadmium. Effluent can possibly be used for establishing tree species of economic value and the soil deterioration can be reduced by giving Some soil treatments.